Calculated times of descent for different turn radii in alpine ski racing - Madura, J. M.; Lufkin, T.; Brown, C. A. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: This work models the influence on time of descent of the choice radius line in ski racing with constant speed and with accelerations due to gravity, ski-snow friction, aerodynamic drag and turn radius. This will help in the selection of line and in the development of technique that can take advantage of the best lines. It also has the potential to assist in the design of courses and equipment that could control the loads on ski racers. There have been several researchers who have measured paths in ski racing (Reid et al. 2008). In the experimental work, while different racers who are taking different turn radii can be compared, it is impossible isolate the influence of the choice of line from technique, strength, snow and equipment factors.